The Influence of Academic Supervision and Teacher's Work Motivation on Teacher’s Competence in MTs Negeri of Palembang - Aisyah, Siti; Fitria, Happy; Eddy, Syaiful (Journal of Social Work and Science Education, 2023)
This study was conducted to describe the effect of academic supervision and teacher work motivation on teacher competence, either partially or simultaneously. The method used in this research is descriptive quantitative. The results achieved from the research that has been done state that partially academic supervision can have a positive and significant influence on teacher competence MTs Negeri throughout Palembang City; as well as with other partial tests that teacher work motivation can have a positive and significant influence on teacher competence; Meanwhile, the simultaneous test stated that academic supervision and teacher work motivation were able to have a positive and significant influence on teacher competence in MTs Negeri throughout Palembang City with a high level of influence.